2020
DOI: 10.1016/j.cej.2019.122809
|View full text |Cite
|
Sign up to set email alerts
|

Facile hydrodynamic cavitation ON CHIP via cellulose nanofibers stabilized perfluorodroplets inside layer-by-layer assembled SLIPS surfaces

Abstract: Access to the published version may require subscription. N.B. When citing this work, cite the original published paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…The best conditions for cavitation generation corresponded to the microfluidic device with short and small sidewall roughness. In another study, Ghorbani et al 24 assessed the potential of a new approach inside microfluidic devices with enhanced surfaces. They characterized the cavitation phenomenon for cellulose nanofiber-stabilized perfluorodroplets (PFC5).…”
Section: Introductionmentioning
confidence: 99%
“…The best conditions for cavitation generation corresponded to the microfluidic device with short and small sidewall roughness. In another study, Ghorbani et al 24 assessed the potential of a new approach inside microfluidic devices with enhanced surfaces. They characterized the cavitation phenomenon for cellulose nanofiber-stabilized perfluorodroplets (PFC5).…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Figures 4-7, the diameter of the craters on the cancer cells in SEM images is approximately 4 µm. Our previous studies [4] show that the size of the collapsing bubbles in cavitating flows in a microfluidic device with similar channel dimensions was around 3.5 µm (See Supplementary Information S2). As a result, it can be concluded that the collapse of cavitating bubbles plays a significant role in the disruption of immobilized cancer cells.…”
Section: B Morphological Change Of Immpobulized Cancer Cells On a Chipmentioning
confidence: 99%
“…Depending on the system geometry and working principle, it generates a high amount of energy upon the collapse of emerging bubbles [2]. Due to a wide variety of potential cavitation applications, many researchers have conducted studies on the cavitation physics to facilitate earlier inception [3], [4] and to intensify cavitating flows [5]. The energy released from the collapse of cavitation bubbles has been effectively employed for various applications such as wastewater treatment [6], food manufacturing [7], energy harvesting [8], [9], bacterial inactivation [10], biomedical treatment [11], and other industrial applications [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Parsa and Zonouzian [156] designed and built a 30 L hydrodynamic cavitation reactor with plates made from scrap iron sheets to degrade Rhodamine B. Recently Ghorbani et al [157] used cellulose nanofibres (CNF) to stabilize perfluorodroplets through Pickering emulsion and "hydrodynamic cavitation on chip." Hydrodynamic cavitation can as well act as an AOP because of the hydroxyl radicals produced.…”
Section: Process Intensification and Kineticsmentioning
confidence: 99%
“…Similarly, Parsa and Zonouzian [ 156 ] designed and built a 30 L hydrodynamic cavitation reactor with plates made from scrap iron sheets to degrade Rhodamine B. Recently Ghorbani et al [ 157 ] used cellulose nanofibres (CNF) to stabilize perfluorodroplets through Pickering emulsion and “hydrodynamic cavitation on chip.” Hydrodynamic cavitation can as well act as an AOP because of the hydroxyl radicals produced. [ 158 ] However, Arrojo and Benito [ 159 ] point out that hydrodynamically generated hydroxyl radicals are more effective at oxidizing volatile and non‐volatile hydrophobic substances as they only promote gas‐phase and gas‐liquid interactions, while it works poorly in liquid‐phase oxidation.…”
Section: Process Intensification and Kineticsmentioning
confidence: 99%